KESESUAIAN DAERAH PENANGKAPAN RAJUNGAN (Portunus pelagicus) MENGGUNAKAN ANALISIS SPASIAL PARAMETER LINGKUNGAN DAN HASIL TANGKAPAN DI PULAU LANCANG - Rahimah, Insaniah; Siregar, Vincentius; Agus, Syamsul (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2019)
The blue swimming crab in the waters of Lancang Island is indicated as being overfished. Hence, the major challenge is managing its utilization in a proper manner. The purpose of this study is to explore the water’s characteristics which is suitable for blue swimming crab fishing. Accordingly, the potential fishing ground around Lancang Island waters can be mapped spatially as an initial effort for species preservation. Geospatial analysis was applied to assess the physical parameters of the existing habitat. The results show that parameters such as MPT, TDS, brightness, phosphate, nitrate, depth and substrate types were remarkably suitable to support the growth of blue swimming crabs. Meanwhile, parameters such as salinity, DO, and temperature show lower quality which implied that the habitat is less suitable. However, the result of weighting and reclassification conclude that Lancang island waters is a decent habitat for blue swimming crab. Catch data show that 40% blue swimming crabs have small carapace size (7-11.83 cm) which is undersized and prohibited by law. Furthermore, about 68% of catch are quite light (30-147 gr) and the sex ratio of males to females was 1:2. It was also revealed that approximately 35% of female species were carrying eggs (BEF/barried female). Keywords: geospatial, fishing ground, suitability, Lancang Island, blue swimming crab.